Quality evaluation of signal grass (Brachiaria brizantha) ensiled with forage as tannin source - B Santoso; B. Tj Hariadi (Indonesian Center for Animal Research and Development (ICARD), 2008)
This research focused on examining the possibility of using three kinds of plant leaves i.e. Acacia mangium Willd, Persea americana Mill and Psidium guajava as tannin source to signal grass (Brachiaria brizantha) silage. The silages were made from the first cut of signal grass harvested at 50 days. Four treatment silages were TA: grass ensiled without tannin as control, AM: grass ensiled with A. mangium (6 g tannin /kg fresh weight), PA: grass ensiled with P. americana (6 g tannin /kg fresh weight), and PG: grass ensiled with P. guajava (6 g tannin/kg fresh weight). After mixing, the materials were packed into glass bottle silos (225 g capacity), in triplicate, which were ensiled for 30 days. The results showed that dry matter, organic matter and crude protein concentrations in signal grass silage mixed with tannin of A. mangium were higher (P<0.01) compared to other silages. Degradations of dry matter, organic matter and crude protein during ensiling were the lowest in silage with A. mangium tannin additive. This data was supported by good fermentation quality of that silage e.g. low pH value, NH3-N and VFA concentrations, and high lactic acid concentration and Fleigh point as compared to other silages. It is concluded that addition of tannin from A. mangium leaf at rate of 6 g/kg fresh weight improved fermentation quality and has potential as protein protection agents during the ensilage of signal grass. Key Words: Fermentation, Silage, Tannin, Signal Grass